Do conspiracy theories efficiently signal coalition membership? An experimental test using the "Who Said What?" design. - Mathilde Mus; Alexander Bor; Michael Bang Petersen (PLoS ONE, 2022)
Theoretical work in evolutionary psychology have proposed that conspiracy theories may serve a coalitional function. Specifically, fringe and offensive statements such as conspiracy theories are expected to send a highly credible signal of coalition membership by clearly distinguishing the speaker's group from other groups. A key implication of this theory is that cognitive systems designed for alliance detection should intuitively interpret the endorsement of conspiracy theories as coalitional cues. To our knowledge, no previous studies have empirically investigated this claim. Taking the domain of environmental policy as our case, we examine the hypothesis that beliefs framed in a conspiratorial manner act as more efficient coalitional markers of environmental position than similar but non-conspiratorial beliefs. To test this prediction, quota sampled American participants (total N = 2462) completed two pre-registered Who-Said-What experiments where we measured if participants spontaneously categorize targets based on their environmental position, and if this categorization process is enhanced by the use of a conspiratorial frame. We find firm evidence that participants categorize by environmental position, but no evidence that the use of conspiratorial statements increases categorization strength and thus serves a coalitional function.